Kendali Tegangan Konverter Boost Berbasis Proposional Integral (PI) - Peri Peri; Muldi Yuhendri (Dinasti Research, 2022)
Technological developments, electronic components and circuits have resulted in a direct voltage supply system that is produced by converting the input DC voltage to another form of DC voltage with a higher output utilizing a boost converter circuit, using a low source voltage where the output voltage can be changed according to user requirements. To anticipate the voltage drop on the output side which is affected by changes in the resistance value of the load and changes in the value of the source voltage, a voltage control is needed that can regulate the output stability of the boost converter. One of the voltage control techniques used is integral proportional controller (PI). This study uses the Ziggler – Nichols oscillation method which is applied to the integral proportional controller (PI) in the boost converter circuit by using the Arduino Mega2650 as a controller circuit which is programmed with Matlab Simulink and a voltage sensor that functions to detect output on the boost converter as well as feedback from the Proportional Integral (PI) controller which will later be compared with the desired setpoint to produce the appropriate Pulse width Modulation (PWM) signal. The test results show that the PI controller works well in accordance with the purpose of adjusting the output voltage on the boost converter. This can be seen in the output of the boost converter which is in accordance with the reference voltage of 15 volts, 20 volts, and 24 volts with an output voltage of 15.36 volts, 20.52 volts, 24.82 volts